KEANEKARAGAMAN DAN AKTIVITAS ENZIMATIS KAPANG RIZOSFER KACANG MEONGAN (Aeschynomene americana L.) DI DESA SUKOLILO BARAT, KECAMATAN LABANG, KABUPATEN BANGKALAN, MADURA - Griffin Natassya; Agung Suprihadi; MG Isworo Rukmi (Jurnal Akademika Biologi, 2013)
Molds are widely distributed in nature, they even present in extreme environment, such as hot and dry soil. Molds which can grow in extreme environment has been adapted to xeric environment by producing enzymes  with  special  characteristics.  The  aim  of  this  study  to  determine  the  diversity  of  molds  from A.americana L. rhizosphere at West Sukolilo Village, Labang district, Bangkalan Regency, Madura and also to examined their cellulolytic and proteolytic activities. Isolation of molds were done by using spread and dilution methods. Molds identification were done by macroscopic and microscopic examined. The molds diversity was calculated using Shannon-Wiener index. Semiquantitative enzyme examination were done using Carboxymethil Cellulose (CMC) agar for cellulolytic ang liquid gelatin 12% for proteolytic. Results of this study showed that mold diversity isolated from   A. americana L. rhizosphere was moderate (1,8-2,7) with total of 43 species, comes from 7 genus i.e. Aspergillus, Penicillium, Fusarium, Aureobasidium, Byssochlamys, Paecilomyces, and Trichoderma.  The  highest  index  of  cellulolytic  produced  by  Aspergillus  sydowii  (2,35),  while  highest proteolytic activity produced by Aspergillus flavus (86%). Keywords : molds, diversity index,xeric, cellulolytic, proteolytic